Clinical outcomes following transapical TAVR with ACURATE neo in the CHANGE neo TA study. (October 2021) - Holzamer, Andreas; Doss, Mirko; Schramm, Rene; Diegeler, Anno; Conradi, Lenard; Strauch, Justus; Holzhey, David; Erlebach, Magdalena; Schröfel, Holger; Arsalan, Mani; Allocco, Dominic J; Hilker, Michael
Abstract: Background: A transapical (TA) approach to transcatheter aortic valve replacement (TAVR) may be used when a transfemoral (TF) approach is not feasible. The CHANGE neo TA study evaluated patients treated in routine clinical practice via TA-TAVR with the ACURATE neo bioprosthetic aortic valve. Methods and results: This single-arm post-market study had a planned enrolment of 200 subjects; enrolment was terminated early due to declining TA-TAVR procedures at participating centers. Final enrolment was 107 patients (mean age: 79.3 years; 54.2% female; mean STS score at baseline: 6.2%). The mortality rate in the intent-to-treat population was 11.2% at 30 days (primary endpoint) and 25.6% at 12 months. The VARC-2 composite endpoint for 30-day safety occurred in 24.3% of patients. Six patients (5.6%) received a permanent pacemaker within 30 days. Site-reported echocardiographic data showed early improvements in mean aortic valve gradient (baseline: 38.8 [SD 13.1] mmHg, discharge: 6.7 [SD 3.7] mmHg) and effective orifice area (baseline: 0.7 [SD 0.2] cm 2, discharge: 1.9 [SD 0.6] cm 2 ), and the discharge rate of paravalvular regurgitation was low (74.7% none/trace, 24.2% mild, 1.1% severe). Conclusions: TA-TAVR with the ACURATE neo valve system yields acceptable clinical outcomes, providing an alternative for patients with aortic stenosis who are not candidates for TF-TAVR.